The Epistemology of Prophet Ibrahim’s Prophetic Leadership in Building a Digital Civilization Generation: A Perspective from Surah Ibrahim Verses 35–41 - Sanjaya, Fiki; Muhammad Ilmiawan; Azzam Taufiqy; Benny Prasetiya (Education Reserach Center, 2026)
This study aims to analyze the epistemology of Prophet Abraham’s prophetic leadership in Surah Ibrahim verses 35–41 within the context of building generations in a digital civilization. The primary focus is to elucidate the epistemological foundations, historical principles, and moral accountability dimensions of prophetic leadership that remain relevant to the challenges of the digital era. The research employs a qualitative method with a library research approach, utilizing textual analysis of the Qur’an through a thematic (maudhu‘i) exegesis perspective and descriptive-interpretive analysis. The data are examined by emphasizing the exploration of the conceptual meanings of verses related to Prophet Abraham’s leadership and their relevance to the formation of generational character in the digital age. The findings indicate that the epistemology of Prophet Abraham’s prophetic leadership is grounded in tawhid as the central paradigm that integrates spiritual, moral, and social dimensions in the construction of civilization. In addition, Prophet Abraham’s leadership embodies a strong historical consciousness through a transgenerational orientation and an emphasis on the continuity of values as a civilizational pillar. The study also identifies the principles of moral accountability and divine validation as key elements affirming that all acts of leadership are situated within a framework of transcendent responsibility. In the context of digital civilization, this epistemology provides a normative framework for developing leadership that is not only based on technological competence but also grounded in spiritual ethics, thereby maintaining a balance between digital advancement and human values.